Association of formulary restrictions and initiation of an SGLT2i or GLP1-RA among Medicare beneficiaries with type 2 diabetes. (May 2022) - Luo, Jing; Gabriel, Nico; Korytkowski, Mary; Hernandez, Inmaculada; Gellad, Walid F.
Abstract: Background: Use of SGLT2 inhibitors (SGLT2i) and GLP-1 receptor agonists (GLP1-RA) among older adults with type 2 diabetes (T2D) has been limited. Objective: To examine factors associated with initiation of an SGLT2i or GLP-1RA among Medicare beneficiaries with T2D in the early years after their market approval, with a particular focus on formulary restrictions (e.g. prior authorization, step therapy requirements, higher co-pays). Methods: A retrospective cohort study using data from a 5% random sample of Medicare beneficiaries with T2D followed from 1/1/2015–12/31/16. Formulary restrictiveness was defined as: (1) the number of target drugs (i.e. SGLT2is or GLP1-RAs) included in tiers 1–3 of a beneficiary's formulary (greater number of drugs in tiers 1–3 being less restrictive) and (2) the number of drugs without prior authorization or step therapy (requirement to try less expensive drugs prior to "stepping up" to more expensive therapies). We used multivariable logistic regression models to estimate the association between measures of formulary restrictiveness and initiation of a target drug, controlling for patient demographics, diabetes duration, clinical comorbidities, and provider specialty. Results: Among 112, 985 beneficiaries with T2D, 5, 619 (5%) initiated an SGLT2i or GLP1-RA. After adjusting for baseline characteristics, patients enrolled in formularies with ≥ 2 target drugs available in tiers 1–3 had 17% higher odds of initiating an SGLT2i or GLP1-RA (aOR 1.17, 95% CI 1.05–1.31) compared to patients enrolled in formularies with 0 drugs available in tiers 1–3. There was no significant association between the number of drugs without prior authorization or step therapy requirements and initiation of a target drug (aOR 0.96, 95% CI, 0.85–1.09). Age 75 years or older (vs < 65, aOR 0.23, 95% CI 0.21–0.26) and black race (vs white, aOR 0.65, 95% CI 0.59–0.71) were associated with lower odds of initiating a target drug. Conclusions: Having a greater number of target drugs available on less expensive formulary tiers is associated with increased odds of initiating an SGLT2i or GLP-1RA among Medicare beneficiaries with T2D.